Johann Heinrich Hottinger and the Systematic Organization of Jewish Literature - Jerchower, Seth; Lerner, Heidi (Judaica Librarianship, 2007)
The authors explore the influence of the Swiss theologian, Orientalist, and Christian Hebraist, Johann Heinrich Hottinger, who preceded Shabbetai Bass in developing and implementing a classified Hebraica-Judaica bibliography. His ideas and theories have heretofore not been closely examined by Judaica bibliographers or researchers of Jewish intellectual history. Hottinger’s innovation was his degree of abstraction: that of analyzing a collection according to its contents. A study of his theories and classification systems can stimulate and encourage a renewed look at early practices and offer insights that can be relevant to current research. Unless otherwise noted, translations from the original Latin, Hebrew, and other languages are the authors’.